Improvement in productivity, nutritional quality, and antioxidative defense mechanisms of sunflower (Helianthus annuus L.) and maize (Zea mays L.) in nickel contaminated soil amended with different biochar and zeolite ratios. (15th July 2018) - Shahbaz, Ali Khan; Lewińska, Karolina; Iqbal, Javed; Ali, Qasim; Mahmood-ur-Rahman; Iqbal, Muhammad; Abbas, Farhat; Tauqeer, Hafiz Muhammad; Ramzani, Pia Muhammad Adnan
Abstract: Nickel (Ni) contaminated soils pose a potential ecological risk to the environment, soil health, and quality of food produced on them. We hypothesized that application of miscanthus biochar (BC) and cationic zeolite (ZE) at various proportions into a Ni contaminated soil can efficiently immobilize Ni and reduce its bioavailability to sunflower ( Helianthus annuus L.) and maize ( Zea mays L.). An electroplating effluent contaminated soil was amended with BC and ZE, as sole treatments (2% w/w) and their combinations of various ratios (BC, ZE, BC25%ZE75%, BC50%ZE50% and BC75%ZE25%) for immobilization of Ni in the soil. Furthermore, the associated effects of these treatments on residual and DTPA-extractable Ni from the soil; concentrations of Ni in shoots, roots, and grain; growth, physiology, biochemistry and the antioxidant defence mechanisms of sunflower and maize were investigated. Results revealed that BC50%ZE50% treatment efficiently reduced DTPA-extractable Ni in the soil, Ni concentrations in shoots, roots, and grain, while improved selective parameters of both plants. Interestingly, the BC75%ZE25% treatment significantly improved the biomass, grain yield, physiology, biochemistry and antioxidant defense machinery, while decreased Ni oxidative stress in both sunflower and maize, compared to rest of the treatments. The results demonstrate that the BC50%ZE50% treatment can efficiently reduce Ni concentrations in the roots, shoots and grain of both sunflower and maize whereas, an improvement in biomass, grain yield, physiological, biochemical, and antioxidant defense machinery of both crops can only be achieved with the application of BC75%ZE25% treatment in a Ni contaminated soil. Highlights: Biochar (BC), zeolite (ZE) and mixtures efficiently immobilized Ni (Nickel) in soil. Significant reduction in soil DTPA-extractable Ni was found in BC50%ZE50% treatment. The BC50%ZE50% significantly reduced Ni concentrations in both sunflower and maize. The physiology, biochemistry and antioxidants in plants were improved in BC75%ZE25%. Oxidative stress was declined in plants treated with BC75%ZE25%.